Kajian Nasi Bekepor: Sejarah, Identitas Budaya, Dan Potensi Pengembangan Sebagai Kuliner Etnis Kutai - Teguh Wicaksono; Marwanti Marwanti (Publikasi Indonesia, 2025)
Nasi Bekepor is one of the culinary heritage of the Kutai ethnic in East Kalimantan, which has historically been an exclusive dish of the Kutai Kingdom. Although it has high cultural value, academic studies that specifically discuss Nasi Bekepor are still very limited. Therefore, this study aims to examine the history, cooking techniques, cultural values, and potential development of bekepor rice as a gastronomic product that can support cultural tourism. This study uses a narrative literature review approach. Data collection is sourced from academic databases such as Scopus and Google Scholar (2010-2025 edition), and enriched with informal interviews to provide local context. The results of the study show that Nasi Bekepor was born from the cultural matrix of the Kutai Kartanegara Sultanate. Originally serving as an exclusive social status marker for the nobility, this dish experienced cultural diffusion to belong to the wider community. Philosophically, the name 'bekepor' (turned) represents a core cooking technique that demands patience. This technique is unique, consisting of three crucial stages: mengaron (cooking half-cooked with spices and vegetable oil instead of coconut milk), mengepor (cooking in a tight way by rotating on coals for 45-60 minutes), and aromatic crust formation. Bekepor rice has a symbolic meaning to the Beseprah Tradition at the Erau Festival, serving as a symbol of the elimination of social barriers and harmony. This study identifies the great potential of Nasi Bekepor in strengthening cultural identity, developing the creative economy for MSMEs, and as the main asset of tourism.